Estratégias para pequenos empreendedores da Moda no Rio de Janeiro: um diagnóstico sobre as dificuldades enfrentadas e as competências empreendedoras fundamentais para superação - Calado, Luiza Silva (2019)
Creative professionals are rejecting formal employment to invest in their own self-employed career. Creative Economy has provided a favorable environment for these individuals to create small businesses that combine their passions and skills. Fashion is considered one of the sectors that make up this new economy, and new initiatives in this field create products with high symbolic value. Many fashion entrepreneurs aim to create a business that leaves a positive legacy for the world. However, these professionals face many difficulties caused by the social, political and economic instability of the country and the state of Rio de Janeiro, which leads to precarious work situations. For these businesses to survive, it is essential that entrepreneurs develop entrepreneurial skills and thus provide the good performance of the enterprise, also seeking to form a network with other entrepreneurs, with the community, educational institutions, government and large companies. Given this, this study aims to relate the entrepreneurial skills that Fashion managers need to improve to ensure the continuity of their enterprises, given the difficulties they face. Therefore, the present study consists of three phases. In the first phase, a descriptive research was made with bibliographic survey and secondary data on Creative Economy; Creative Entrepreneurship and the scenario of the economic, political and socio-cultural crisis of Brazil and Rio de Janeiro; Fashion; and Entrepreneurial Behaviors and Skills. In the second phase, three specialists in the area of competences were interviewed, in order to understand in more depth which are the entrepreneurial skills that are fundamental to the good performance of a fashion business. In the third phase, 10 fashion entrepreneurs were interviewed to identify the causes of the main difficulties they faced and which were the most relevant skills for their business to survive. As a result, we realized that entrepreneurs who had contact with entrepreneurship programs focused on creative enterprises, developed various entrepreneurial skills and thus managed to mitigate the main adversities. In addition, we identified a group of 17 key entrepreneurial skills for Fashion managers, an academic contribution of this research. Finally, it was possible to make a practical contribution to managers of creative industries: a roadmap that establishes a relationship between the difficulties caused by different causes, and the entrepreneurial skills that managers need to develop to succeed